Pelatihan peningkatan kosakata Bahasa Inggris menggunakan YouTube - Muhammad Asrul Sultan; Nurjannah Nurjannah; Ahmad Subair (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Youtube is one of the social media that is very developed at this time which has been generally discussed ranging from children to adults. Given the importance of equipping our children about the use of technology that has often been mistaken in its use. Vocabulary enhancement training using YouTube is one of the ways to reduce the negative impact of using social media, especially YouTube. The training was carried out by PGSD lecturers at Makassar State University and several students. This training activity is a training conducted to improve the English vocabulary of the students of the recitation of the mMasjid Babul Ilmi, Parepare Campus, Makassar University.